Thermoeconomic analysis method for optimization of combined heat and power systems - part II - Silveira, J. L.; Tuna, C. E. (Elsevier B.V., 2004)
In this paper, a thermoeconomic functional analysis method based on the Second Law of Thermodynamics and applied to analyze four cogeneration systems is presented. The objective of the developed technique is to minimize the operating costs of the cogeneration plant, namely exergetic production cost (EPC), assuming fixed rates of electricity production and process steam in exergy base. In this study a comparison is made between the same four configurations of part I. The cogeneration system consisting of a gas turbine with a heat recovery steam generator, without supplementary firing, has the lowest EPC. (C) 2004 Published by Elsevier Ltd.
Keywords: thermoeconomic; exergy; cogeneration; cost equations; functional analysis